2007
DOI: 10.1111/j.1944-9720.2007.tb03201.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Foreign Language Classroom Anxiety Scale Measuring Anxiety or Language Skills?

Abstract: Fifty‐four students were followed over 10 years and tested with native language measures in first through fifth grades and measures of foreign language aptitude and foreign language proficiency in high school. All students had completed two years of Spanish, French, or German. Students were divided into three groups based on their scores on the Foreign Language Classroom Anxiety Scale (FLCAS). Findings showed that the low anxious group scored significantly higher than the high anxious group on all native langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
110
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 46 publications
15
110
0
7
Order By: Relevance
“…According to Ganschow (1993, 2007), anxiety arises from poor achievement and not the other way round. They argued that the early first language (L1) literacy achievement of individuals is a strong predictor of both their L2 proficiency and anxiety in the future (Sparks & Ganschow, 2007). In this view, low performance, stemming from linguistic processing disability, is considered the cause of anxiety and not the result.…”
Section: Debates On the Direction Of The Causal Relationship Between mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ganschow (1993, 2007), anxiety arises from poor achievement and not the other way round. They argued that the early first language (L1) literacy achievement of individuals is a strong predictor of both their L2 proficiency and anxiety in the future (Sparks & Ganschow, 2007). In this view, low performance, stemming from linguistic processing disability, is considered the cause of anxiety and not the result.…”
Section: Debates On the Direction Of The Causal Relationship Between mentioning
confidence: 99%
“…Since its publication, FLCAS has become the most widely used standard measure of anxiety in anxiety literature. It should be noted that, while Sparks and Ganschow (2007) claimed that FLCAS measures language skills rather than the anxiety level, in support of FLCAS, Young (1994, p. 3) stated that since the publication of the FLCAS, "the concept of anxiety in second language acquisition has achieved the status of a precise technical notion". Furthermore, since the use of Horwitz et al's (1986) FLCAS, researchers have found relatively consistent findings related to the negative associations between FLA and language performance (e.g.…”
Section: Research Questionsmentioning
confidence: 99%
“…From this perspective, they claim that language anxiety is unique due to the way it involves learners' self-concepts to communicate competently and to present themselves genuinely. Foreign language anxiety can occur if students are exposed to several negative experiences in a foreign language context (Chen and Chang, 2004;Sparks et al, 2000;Hewitt and Stephenson, 2012;Horwitz et al, 1986;Horwitz et al, 2010;MacIntyre and Gardner, 1991;MacIntyre, 1999;Saadi, 2009;Sparks and Ganschow, 2007). Moreover, it can "make learners get discouraged, lose faith in their abilities, escape from participating in classroom activities, and even give up the effort to learn a language well" (Na, 2007).…”
Section: Authors Agree That This Article Remain Permanently Open Accementioning
confidence: 99%
“…According to this definition, individuals may feel a threat to their self-image because they have to engage in tasks in the foreign language over which they have a poor command. Results of the recent research indicated that anxiety was often reported to be an important cause for decreased learning motivation, interference with the learning process, and poor performance (Elkhafaifi, 2005;Pappamihiel, 2002;Sparks & Ganschow, 2007).…”
Section: Foreign Language Anxietymentioning
confidence: 99%